Hybrid Schedule Management in 6TiSCH Networks: The Coexistence of Determinism and Flexibility - Abdulkadir Karaagac; Ingrid Moerman; Jeroen Hoebeke (IEEE Access, 2018)
With the emergence of the Internet of Things (IoT), Industry 4.0, and cyber-physical system concepts, there is a tremendous change ongoing in industrial applications, which is imposing increasingly diverse and demanding network dynamics and requirements with a wider and more fine-grained scale. The purpose of this paper is to investigate how a hybrid schedule management in 6TiSCH architecture can be used to achieve the coexistence of applications with heavily diverse networking requirements. We study the fundamental functionalities and also describe network scenarios, where such a hybrid scheduling approach can be used. In addition, we present the details about the design and implementation of the first 6TiSCH centralized scheduling framework based on CoAP management interface (CoMI). We also provide theoretical and experimental analysis, where we study the cost of schedule management operations and illustrate the operation of the CoMI-based 6TiSCH schedule management.